A Community Based Cross-Sectional Study on Gender Differences in Cancer Awareness Among Rural Population in South India - Rushender Chitharaj, Rajan; Kumar Ganesan, Dinesh; Boopathirajan, RamKumar; Kumar Krishnan, Gokul (Indian Journal of Community Health, 2019)
Background: Cancer is one of the major non communicable diseases and in India, there is a lack of awareness regarding cancer symptoms and their screening methods especially among women in rural areas Aim & Objective: To assess the gender differences in the cancer awareness among the study population. Settings and Design: Community based cross-sectional study was conducted in the field practice area of department of community medicine on 414 adults selected by systematic random sampling. Methods and Material: The awareness level regarding the etiology, common sites, presenting complaints, mode of diagnosis, treatment, prevention & methods of prevention of cancer and relationship between gender and awareness levels were evaluated Statistical analysis: Chi-square test was used to study the association between knowledge and gender Results: A total of 414 subjects were included in the final analysis. Majority (55.80%) were females. In the study, 94.69% had heard of cancer and mostly (60.87%) through Television. Breast (11.4%), Oral (10.9%) and other sites (48.1%) were the commonly known sites of cancers. Conclusion: There was no significant difference in knowledge regarding cancer site, cause, treatment and prevention between females and males.